Introduction to Banach algebras, operators, and harmonic analysis - Dales, H. G. (Harold G.), 1944- (London Mathematical Society student texts, 2003)
Arising from lecture courses given by the authors, this book gives introductions to important topics in functional analysis at a level ideal for beginning graduate students as well as others interested in the subject. The collection is carefully written to form a coherent and accessible introduction to current research topics.